The Role of Artificial Intelligence and HR Analytics in Enhancing Strategic Human Resource Decision-Making - Muhammad Bakri; Yassir Yassir (Advances: Jurnal Ekonomi & Bisnis, 2026)
Purpose: This study aims to systematically analyze the roles of Artificial Intelligence (AI) and HR Analytics in enhancing strategic human resource decision-making, focusing on their integration, impact, and implementation challenges. Research Method: This research employs a Systematic Literature Review (SLR) to analyze peer-reviewed journal articles on AI, HR Analytics, and strategic HR decision-making. Relevant studies were identified, screened, and synthesized to ensure a structured and comprehensive evaluation. Results and Discussion: The findings indicate that AI and HR Analytics significantly enhance decision quality, speed, and predictive accuracy, enabling a shift from reactive to proactive decision-making. HR Analytics plays a mediating role in transforming workforce data into actionable insights. However, the impact varies depending on organizational readiness, data quality, and analytical capability. Key challenges include data integration, skill gaps, and ethical concerns such as algorithmic bias and transparency. Implications: This study provides theoretical contributions by offering an integrated framework linking AI, HR Analytics, and strategic decision-making. Practically, organizations should strengthen data governance, analytical capabilities, and leadership support to maximize the benefits of AI-driven HR systems. Originality: This study offers originality by integrating AI and HR Analytics into a unified framework that explains how both technologies support strategic human resource decision-making while addressing organizational and ethical implementation challenges.